РАЗВИТИЯ ГИБКОСТИ У ДЕВОЧЕК 8-10 ЛЕТ НА ЗАНЯТИЯХ ХУДОЖЕСТВЕННОЙ ГИМНАСТИКОЙ - Ешбаев, А.Ж.; Утениязова, Ш.Б. (SCIENCE and SOCIETY, 2023)
A set of exercises has been developed to develop the flexibility of gymnasts. In rhythmic gymnastics, at the stage of initial training, one of the important part is the development of flexibility. Flexibility is an important psychophysical quality, which, together with speed, strength, endurance, dexterity, finds its definition in the morphofunctional biological characteristics of a person.
Keywords: rhythmic gymnastics; educational and training process; initial training; special physical training